Protein Phosphatase 2A and Its Methylation Modulating Enzymes LCMT-1 and PME-1 Are Dysregulated in Tauopathies of Progressive Supranuclear Palsy and Alzheimer Disease. Issue 2 (21st December 2017) - Park, Hye-Jin; Lee, Kang-Woo; Oh, Stephanie; Yan, Run; Zhang, Jie; Beach, Thomas G; Adler, Charles H; Voronkov, Michael; Braithwaite, Steven P; Stock, Jeffry B; Mouradian, M Maral
Abstract: Hyperphosphorylated tau aggregates are characteristic of tauopathies including progressive supranuclear palsy (PSP) and Alzheimer disease (AD), but factors contributing to pathologic tau phosphorylation are not well understood. Here, we studied the regulation of the major tau phosphatase, the heterotrimeric AB55αC protein phosphatase 2 A (PP2A), in PSP and AD. The assembly and activity of this PP2A isoform are regulated by reversible carboxyl methylation of its catalytic C subunit, while the B subunit confers substrate specificity. We sought to address whether the decreases in PP2A methylation and its methylating enzyme, leucine carboxyl methyltransferase (LCMT-1), which are reported in AD, relate to tau pathology or to concomitant amyloid pathology by comparing them in the relatively pure tauopathy PSP. Immunohistochemical analysis of frontal cortices showed that methyl-PP2A is reduced while demethyl-PP2A is increased, with no changes in total PP2A or B55α subunit, resulting in a reduction in the methyl/demethyl PP2A ratio of 63% in PSP and 75% in AD compared to controls. Similarly, Western blot analyses showed a decrease of methyl-PP2A and an increase of demethyl-PP2A with a concomitant reduction in the methyl/demethyl PP2A ratio in both PSP (74%) and AD (76%) brains. This was associated with a decrease in LCMT-1 and an increase in the demethylating enzyme, protein phosphatase methylesterase (PME-1), in both diseases. These findings suggest that PP2A dysregulation in tauopathies may contribute to the accumulation of hyperphosphorylated tau and to neurodegeneration.